Two new species of the Genus Clathria (Demospongiae: Poecilosclerida: Microcionidae) from Jeju Island, Korea - Kang, Dong Won; Kim, Hyung June (Zootaxa, 2018)
Two new species of sponge, Clathria (Clathria) ramus sp. nov. and Clathria (Clathria) ieoensis sp. nov. are described from Jeju Island of Korea. Clathria (Clathria) ramus sp. nov. is branching with a stalk, yellow in life, with small oscules. Clathria (C.) ieoensis sp. nov. is thickly encrusting, soft and compressible texture, and color is red and dark brown after fixation in ethanol. The new species are compared to other microcionids from the Korean region, and similar species from elsewhere.